Plasma Copeptin Levels in Autosomal Dominant Polycystic Kidney Disease - Vaishnavi Venkatasubramanian; Jasmine Sethi; Jaskiran Kaur; Ashok Kumar Yadav; Vivek Kumar (Indian Journal of Kidney Diseases)
Introduction: In autosomal dominant polycystic kidney disease (ADPKD), vasopressin is associated with accelerated growth of total kidney volume (TKV) and loss of estimated glomerular filtration rate (eGFR). Plasma copeptin is released along with vasopressin in equimolar concentration and hence considered a validated surrogate for vasopressin that is easy to measure and relatively stable. This study was conducted with the objective of determining the association of plasma copeptin with kidney volume and eGFR. Methods: This was an observational trial conducted at a tertiary care center of northern India between January 2022 and July 2023. We included consecutive ADPKD patients aged between 15 and 60 years with a nonrapidly progressive disease at baseline (Mayo Class 1A–C). Serum copeptin levels were measured at baseline and 6 months by human copeptin ELISA kits. Height-adjusted TKV (htTKV) was estimated at baseline and 6 months using the ellipsoid equation using noncontrast computed tomography. Results: The mean (standard deviation [SD]) age of the cohort (n = 37) was 37.37 (10.02) years with 48% being male. Hypertension was present in nearly one half of the cohort. Around 2/3rd (59.5%) of the patients had a positive family history of ADPKD. The mean (SD) serum creatinine was 0.90 (0.27) mg/dL and mean (SD) baseline eGFR was 98.29 (26.54) mL/min/1.73m2. Around 16.2% of patients had moderately increased proteinuria (A2). The mean baseline htTKV was 336.13 (152.41) (mL/m with 16.2% of the patients in Mayo Class 1C. The mean (SD) 6 monthly decline in eGFR was − 0.47 (15.9) mL/min/1.73 m2 and the mean (SD) 6 monthly increase in htTKV was 28.27 (125.41) mL/m. There was no correlation of baseline copeptin with age, sex, eGFR, and htTKV at baseline. The mean eGFR and htTKV differences at 6 months were not significantly different among the quartiles of baseline copeptin levels (P = 0.669 and 0.570). There was no correlation of baseline copeptin levels and eGFR and htTKV difference at 6 months. Conclusions: Our study showed no correlation of baseline copeptin levels htTKV difference or eGFR difference at 6 months. Larger, long-term studies with diverse patient populations and detailed clinical phenotyping may be necessary to definitively establish the role of copeptin as a prognostic biomarker in ADPKD.